Does combination of Lactobacillus rhamnosus Heriz I and beta glucan improve quality of life in women with breast cancer receiving chemotherapy?: A randomized double-blind placebo-controlled clinical trial. Issue 3 (18th September 2019) - Monshikarimi, Alireza; Ostadrahimi, Alireza; Asghari Jafarabadi, Mohammad; EivaziZiaei, Jamal; Barzeghari, Abolfazl; Esfahani, Ali; Payahoo, Laleh; Aamazadeh, Fatemeh; Farrin, Nazila
Abstract : Purpose: This paper aims to study the impact of combination Lactobacillus Rhamnosus Heriz I and Beta glucan on quality of life (QOL) in breast cancer (BC) patients receiving chemotherapy. Design/methodology/approach: In all, 30 women with BC were enrolled in this randomized double-blind placebo-controlled clinical trial. Intervention group received either daily one capsule of L. rhamnosus strain Heriz I (2 × 10 7 CFU) and two 10-mg capsules of soluble1–3, 1–6, D-beta glucan and the placebo group receiving placebo, interval between two courses of chemotherapy. Health-related QOL was evaluated at baseline and end of the trial using the EORTC QOL Questionnaire version.3.0 (EORTC QLQ-C30). Findings: The results showed that combination of L. rhamnosus Heriz I and Beta glucan supplementation in BC patients during chemotherapy improved functional scales score from 37.3 ± 12.1 to 39.8 ± 6.8 and this increase in comparison with placebo was significant after adjusting baseline value ( p = 0.015). Changes in symptoms scores were not significant after intervention ( p = 0.05) but the decreased score (66.1 ± 12.9 to 60.6 ± 9.4) was considerable clinically. As well as, changes in global health status/QOL score in intervention group in comparison with the placebo group was not significant ( p = 0.93). Originality/value: The findings suggest that combination of L. rhamnosus Heriz I and Beta glucan may be associated for improving functional scales and symptoms in patients with BC who underwent chemotherapy. To prove positive effect of supplements on other aspects of QOL, further studies are needed.